Problems of calculation of the terms of appeals of decisions made in the order of summary proceedings - N. G. Galkovskaya (Правоприменение, 2023)
The subject of the research is the features of the appeal of court decisions in cases considered in summary proceedings.The methodology. Analysis and synthesis, dialectical method as well as formal legal interpretation of Russian legislative acts.The main results. The author critically assesses the provisions of the procedural legislation, focuses on the problems that exist in practice. (1) There is a different procedure for notifying a decision adopted as a result of summary proceedings, according to the norms of the Civil Procedure Code and of the Arbitration Procedure Code. (2) It is concluded that the dependence of the beginning of the period for filing an application for drawing up a reasoned decision on the day of placement of the operative part of the decision or on the day of its adoption significantly complicates the timely implementation of such a right. A different construction will be justified and practically convenient: fixing in the law a single moment of the beginning of the period for an appeal against a decision - from the moment a copy of the operative part is delivered (irrespective of the application for drawing up a reasoned decision). (3) If the deadline for filing an application for the preparation of a reasoned decision is missed, the issue of its restoration should be resolved only if the deadline for filing an appeal has not been missed. If the deadline for filing an appeal is missed, then a reasoned decision on the case should be made only if the specified dead-line is restored.Recommendations are offered on the possible improvement of procedural rules on summary proceedings. In particular, the issue of increasing the period for applying for a reasoned decision was raised. It is proposed that the start time for filing an application for the preparation of a reasoned decision be determined from the day a copy of the decision is handed over to the persons participating in the case, or the decision is posted on the court's website.Conclusions. The identified problems call into question the merits of the summary procedure, show in practice its difficult and complicated order. The existing model of summary proceedings needs to be significantly detailed in order to increase the guarantees of judicial protection.